Constraints in adoption of Acacia mangium – A case study in Konkan region of Maharashtra - Shigwan, Ashish; Dalvi, V.V.; Meshram, N.A. (Indian Journal of Agroforestry, 2020)
The present study was conducted in Kasu village of Raigad District of Maharashtra. The data were collected from 60 farmers through structured questionnaire method. The constraints faced by Acacia mangium growers were identified by asking them to indicate the problems in the areas of credit/loan, labour, inputs, technology and marketing aspects, respectively. The farmers felt that the non-availability of agricultural labour was the primary reason lead to 85% for opting A.mangium plantation, followed by high income within a short period (75%). Among the difficulties, non-availability of credits/loan was the major constraint of farmers having 88.33%. In the category of input constraints, the major constraints were faced by majority of mangium growers in the cost of fertilizers (75%). More than 60% mangium growers reported that, prior permission from forest department should require for felling of trees. The mangium growers suggested for provision of loan and subsidies, keeping the process of inputs like fertilizers and insecticides reasonable. The government should lift the ban on obtaining prior permission for felling of trees planted by them on their field. If this is done, it will be helpful to increasing the adoption of mangium cultivation.